Assessing the ultimate uplift capacity of plate anchors in geocell-reinforced sand. Issue 6 (20th August 2018) - Rahimi, M.; Leshchinsky, B.; Moghaddas Tafreshi, S. N.
Abstract : Use of geosynthetic reinforcement may improve the performance of many geotechnical systems, including anchors. In this study, the uplift capacity of geocell-reinforced sand is studied based on a series of near large-scale experiments and calibrated three-dimensional Finite Element (FE) models. Using the verified FE models, a comprehensive parametric study of over 270 models was performed to assess the influence of friction angle, geocell stiffness, embedment depth, anchor size, and geocell-anchor width ratios on uplift capacity. Uplift capacity increases with embedment depth and friction angle, but the relative increase is more pronounced for loose sand. The observed shape effects are amplified in reinforced installation. The increase in uplift capacity observed decays for geocell-anchor width ratios greater than 3, but an increase in geocell stiffness demonstrates increased uplift capacity through the increased mobilization of geocell resisting uplift. Finally, based on the verified numerical models, a semi-empirical equation is proposed to enable estimation of uplift capacity in geocell-reinforced sand, demonstrating good agreement with results from numerical simulations.